Efficacy of levetiracetam in STXBP1 encephalopathy with different phenotypic and genetic spectra. (February 2022) - Wang, Qiu-Hong; Cao, Jia-Jie; Wang, Yang-Yang; Zhang, Meng-Na; Liu, Li-Ying; Wang, Jing; Lu, Qian; He, Wen; Shen, Yan-Wen; Chen, Hui-Min; Luo, Xiao-Mei; Chen, Qian; et al.
Highlights: There are 40 patients carrying STXBP1 variants, and the usage of ASMs in 37 patients were analyzed. Levetiracetam treatment can increase the seizure reduction rate but not seizure freedom in patients with STXBP1-E. Levetiracetam monotherapy could achieve seizure freedom in other EOEE rather than refractory WS or OS. Levetiracetam showed different efficacy in different functional areas of STXBP1. Abstract: Objective: Syntaxin binding protein 1 (STXBP1) plays an important role in the release of synaptic vesicles. STXBP1 -related encephalopathy is a brain dysfunction caused by STXBP1 variation. Levetiracetam (LEV) exerts antiepileptic effects by binding to synaptic vesicle protein 2A (SV2A). This study aimed to analyze the prognosis of LEV treatment of STXBP1 encephalopathy ( STXBP1 -E) and the correlation among genotype, phenotype, and LEV efficacy. Methods: Patients with pathogenic STXBP1 variants were collected from multiple centers, and their clinical history, video electroencephalogram (vEEG) characteristics, imaging examination data, and anti-seizure medication (ASM) history were systematically analyzed. The ASMs related to the prognosis were explored. Results: Forty patients with STXBP1 -E were enrolled in this study. The detailed ASM usage of 37 patients was recorded without intervening in ASM selection. At the endpoint of six months treatment, the results of Fisher's exact test showed that in all ASMs, LEV affected the prognosis of patients with STXBP1 -E. LEV was effective in improving the partial remission rate but did not achieve seizure freedom. However, LEV monotherapy could achieve seizure freedom in patients with other early-onset epileptic and encephalopathy. For refractory West syndrome (WS) or Ohtahara syndrome (OS), LEV combined with other ASMs could improve the seizure remission rate. Conclusion: LEV increased the seizure reduction rate and improved the vEEG characteristics in patients with STXBP1 -E, but not seizure freedom. LEV combined with other ASMs could increase the seizure reduction rate, especially for refractory WS or OS. Thus, LEV could be considered after identifying the pathogenicity of STXBP1 variants.